Development of Pujan Kasanga Tengger Literary Tourism in Tengger Villages, Tosari District, Pasuruan Regency - Sukmawan, Sony; Setiawati, Eti; Mumtaz , Tsabitah Zain; Isna , Fariha Nurul; Litanjua, Barirta; Nafisah, Putri Kholifatun; Putra, Muhammad Zanika Esa; Bilkis, Kinamin Mutiara (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
The rich tradition and diversity of oral traditions of the people of Tengger Village, Tosari District, has actually become one of the supporting media in the development of the tourism sector. The concept of tourism combined with oral traditions can become a potential resource. However, human resources as supporting the existence of tourism have not been prepared and empowered to the fullest. For this reason, the solution to the problem offered to overcome this problem is to determine the characteristics of tourism based on the potential of local wisdom; preparing human resources with provision of traditional documentation, as well as provision of digital literacy skills; transfer of the Pujan kasanga tradition and orality phenomena related into digital illustrated stories; as well as ongoing assistance for the development of literary tourism based on the Pujan Kasanga tradition. Target audiences that can be partners in this service are traditional priesthoods, village government, art groups, pradah youth groups, and the local community. The expected outcomes of this community activity are the identification of the potential and manifestation of local wisdom through the basis for determining the characteristics of the Tengger Villages, Tosari District, the ability to document local cultural potential, the ability to use and publish fairy tales through digital platforms, the publication of illustrations and descriptions of Pujan Kasanga and more concrete and interesting illustrated fairy tales on digital media. This service is expected to be of benefit to the people of Tengger Village, Tosari District in terms of improving the economy and increasing public awareness regarding the importance of preserving and exploiting cultural potential.